Electrolytic hydrogenation catalyst, preparation method and application thereof
By using nitrogen-doped porous carbon materials to support transition metal nanoparticles in electrolytic water hydrogen production technology, the problem of high cost and poor stability of precious metal catalysts is solved, and efficient and stable electrocatalytic water decomposition and hydrogen production effect is achieved.
Patent Information
- Application Number
- CN202411720563.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-04-08
AI Technical Summary
In the existing electrolytic hydrogen production technology, precious metal catalysts have problems such as small reserves, high costs, and difficulty in large-scale application. Non-precious metal catalysts are prone to oxidation in the air, have poor stability, complex synthesis process, and high cost.
An electrolytic hydrogen catalyst with nitrogen-doped porous carbon material supported by transition metal nanoparticles is obtained by solvothermal reaction and heat treatment. The nitrogen-doped porous carbon material provides a loading site and protects transition metal nanoparticles, improving catalytic activity and stability.
It has achieved efficient electrocatalytic water decomposition and hydrogen production, and the catalyst has excellent electrocatalytic activity and stability, and has great potential for industrial application.
Smart Images

Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application specifically relates to an electrolytic hydrogen decomposition catalyst, a preparation method thereof, and an application thereof in an electrocatalytic water decomposition hydrogen production process. Background Art
[0002] At present, the main technologies for producing hydrogen by electrolysis of water include alkaline water electrolyzer (AE), proton exchange membrane water electrolyzer (PEM) and solid oxide water electrolyzer (SOE), etc. Among them, AE technology is the most mature and has relatively low production cost.
[0003] The electrolytic hydrogenation catalysts used in traditional AE technology are mainly precious metal catalysts, which have the problems of small reserves, high cost, and difficulty in large-scale application. In recent years, some researchers have tried to use transition metals such as nickel to replace precious metal catalysts. However, non-precious metal electrolytic hydrogenation catalysts have the following defects in practical applications: transition metal catalysts are easily oxidized in the air and difficult to exist stably; transition metal catalysts are difficult to work stably for a long time under actual working conditions; the synthesis process of transition metal catalysts is complicated and costly. Summary of the invention
[0004] The main purpose of the present application is to provide an electrolytic hydrogen evolution catalyst, a preparation method and application thereof, so as to overcome the deficiencies of the prior art.
[0005] In order to achieve the above invention objectives, this application adopts the following technical solutions: The first aspect of the present application provides an electrolytic hydrogen evolution catalyst comprising: Nitrogen-doped porous carbon materials; first catalytically active particles, which are distributed on the surface of the nitrogen-doped porous carbon material, and include first transition metal nanoparticles and a transition metal oxide layer coated on the surface of the first transition metal nanoparticles; The second catalytically active particles are distributed in the pores contained in the nitrogen-doped porous carbon material and include second transition metal nanoparticles.
[0006] In one embodiment, the molar ratio of the C element to the N element in the nitrogen-doped porous carbon material is 100:5-15, the porosity is 80-95%, and the pore size of the contained pores is 30-150 nm.
[0007] In one embodiment, the particle size of the nitrogen-doped porous carbon material is 1-100 μm.
[0008] In one embodiment, the materials of the first transition metal nanoparticles and the second transition metal nanoparticles include copper, iron, nickel, titanium or cobalt, but are not limited thereto.
[0009] In one embodiment, the particle size of the first transition metal nanoparticles and the second transition metal nanoparticles is 5-100 nm.
[0010] In one embodiment, the thickness of the transition metal oxide layer is 5-10 nm.
[0011] In one embodiment, the mass ratio of the total mass of the first catalytically active particles and the second catalytically active particles in the electrolytic hydrogen decomposition catalyst to the nitrogen-doped porous carbon material is 1:10-100.
[0012] The second aspect of the present application provides a method for preparing the electrolytic hydrogen evolution catalyst, comprising: subjecting a mixed reaction system comprising a nitrogen-doped porous carbon material, a soluble transition metal salt, a small molecule organic acid salt, water and an organic solvent to a solvothermal reaction at 150-250° C. for 0.5-12 hours, and then separating the solid matter in the obtained reaction mixture, washing and vacuum drying the solid matter in sequence, and then heat treating the solid matter in air at 250-400° C. for 10-30 minutes to obtain the electrolytic hydrogen evolution catalyst.
[0013] In one embodiment, the preparation method specifically comprises: Dissolving a small molecule organic acid salt in water to form a small molecule organic acid salt solution; dispersing or dissolving a soluble transition metal salt in an organic solvent or a mixture of an organic solvent and water to form a soluble transition metal salt solution; A nitrogen-doped porous carbon material, a small molecule organic acid salt solution and a soluble transition metal salt solution are added into a sealed reactor and uniformly mixed, and then a solvent thermal reaction is carried out at 150-250° C. for 0.5-12 hours. The solid matter in the obtained reaction mixture is then separated by centrifugation or filtration, and then washed with a polar organic solvent, washed with water, and vacuum dried in sequence, and then heat treated in air at 250-400° C. for 10-30 minutes to obtain the electrolytic hydrogenation catalyst.
[0014] Furthermore, the mixed reaction system is a liquid phase reaction system, and in the reactor, the nitrogen-doped porous carbon material is uniformly dispersed in the liquid phase reaction system.
[0015] Furthermore, after the mixed reaction system is added into the reactor, the reaction filling ratio is 50-80%.
[0016] Furthermore, when performing the solvothermal reaction, the mixed reaction system is preferably subjected to ultrasonic treatment.
[0017] In one embodiment, the mass ratio of the nitrogen-doped porous carbon material, the soluble transition metal salt, the small molecule organic acid salt, water and the organic solvent is 10-100:1-2:1-2:10-600:10-300.
[0018] In one embodiment, the soluble transition metal salt is at least selected from chlorides, nitrates, sulfates or organic acid salts of copper, iron, nickel, titanium or cobalt, such as nickel chloride, ferric chloride, copper chloride, cobalt chloride, nickel sulfate, ferric sulfate, copper sulfate, cobalt sulfate, nickel nitrate, copper nitrate, cobalt nitrate, nickel acetylacetonate, etc., and is not limited thereto.
[0019] In one embodiment, the small molecule organic acid salt includes sodium formate, potassium formate, sodium acetate or potassium acetate, but is not limited thereto.
[0020] In one embodiment, the organic solvent includes tetrahydrofuran (THF), acetonitrile, ethanol, N,N-dimethylformamide (DMF) or dimethyl sulfoxide (DMSO), etc., but is not limited thereto.
[0021] The third aspect of the present application provides a method for producing hydrogen by electrocatalytic water decomposition, wherein the working electrode used in the method includes the electrocatalytic hydrogen decomposition catalyst.
[0022] Compared with the prior art, this application has at least the following beneficial effects: (1) The electrolytic hydrogen evolution catalyst of the present application utilizes nitrogen-doped porous carbon materials to load transition metal nanoparticles, which can provide abundant loading sites on the one hand, and can provide good protection for the transition metal nanoparticles on the other hand. In particular, the transition metal nanoparticles located on the surface of the nitrogen-doped porous carbon material have a transition metal oxide coating layer formed on the surface, which has both high electrocatalytic activity and stability. The transition metal nanoparticles located inside the nitrogen-doped porous carbon material retain high catalytic activity while being protected by the nitrogen-doped porous carbon material and are not easily deactivated. On the other hand, heterojunctions with different two-dimensional electron gas concentrations can be formed between the nitrogen-doped porous carbon material and the transition metal nanoparticles with a transition metal oxide coating layer formed on the surface and the transition metal nanoparticles with no oxide coating on the surface, so that the overall catalytic activity is further improved when the power is on, thereby exhibiting excellent electrocatalytic activity and stability.
[0023] (2) The electrolytic hydrogen evolution catalyst of the present application can be assembled and applied in a water electrolysis hydrogen production device, works well and stably, and has great potential for industrial application. DETAILED DESCRIPTION
[0024] The following describes the implementation of the present application through specific embodiments. People familiar with this technology can easily understand other advantages and effects of the present application from the contents disclosed in this specification.
[0026] Example 1 Weigh 0.5 g of sodium formate and add it to 3 ml of ultrapure water to obtain a sodium formate solution.
[0027] Weigh 0.5 g of NiCl2·6H2O and add it to 25 ml of DMF and dissolve it by ultrasonication to obtain a nickel chloride solution.
[0028] 5 g of nitrogen-doped porous carbon material (purchased from Pioneer Nano, XFP14), the above-mentioned sodium formate solution and the above-mentioned nickel chloride solution were mixed and ultrasonically vibrated evenly, then added into a 50 ml polytetrafluoroethylene reactor, sealed, and placed in a programmed temperature oven with a heating rate of 5°C / min. The reaction was carried out at 180°C for 8 h, cooled to room temperature, and the solids in the reaction mixture were separated by centrifugation. The solids were washed alternately with water and ethanol for 3 times, vacuum dried at 60°C for 12 h, and then heat treated in air at 250°C for 15 min to obtain an electrolytic hydrogen evolution catalyst, which was defined as product 1.
[0029] Comparative Example 1 The preparation method of an electrolytic hydrogen evolution catalyst (defined as comparative product a) provided in this comparative example is basically the same as that of Example 1, except that the nitrogen-doped porous carbon material is replaced by a porous carbon material (purchased from Pioneer Nano, XFP05).
[0030] Comparative Example 2 The preparation method of an electrolytic hydrogen evolution catalyst (defined as comparative product b) provided in this comparative example is substantially the same as that of Example 1, except that the step of heat-treating the product of the dissolved thermal reaction in air is omitted.
[0031] Example 2 Weigh 0.3 g of sodium acetate and add it to 10 ml of ultrapure water to obtain a sodium acetate solution.
[0032] Weigh 0.5 g of copper sulfate and add it to 20 ml of DMSO for ultrasonic dissolution to obtain a copper sulfate solution.
[0033] 10 g of nitrogen-doped porous carbon material (purchased from Pioneer Nano, XFP14), the above-mentioned sodium acetate solution and the above-mentioned copper sulfate solution were mixed and ultrasonically vibrated evenly, then added into a 50 ml polytetrafluoroethylene reactor, sealed, and placed in a programmed temperature oven with a heating rate of 2°C / min. The mixture was reacted at 150°C for 12 h, cooled to room temperature, and the solids in the reaction mixture were separated by centrifugation. The mixture was washed alternately with water and ethanol for 3 times, vacuum dried at 60°C for 6 h, and then heat treated in air at 400°C for 10 min to obtain an electrolytic hydrogen evolution catalyst, which was defined as product 2.
[0034] Example 3 Weigh 0.2 g of sodium formate and add it to 5 ml of ultrapure water to obtain a sodium formate solution.
[0035] Weigh 0.1 g of nickel acetylacetonate and add it to 15 ml of acetonitrile for ultrasonic dissolution to obtain a nickel acetylacetonate solution.
[0036] 5 g of nitrogen-doped porous carbon material (purchased from Pioneer Nano, XFP14), the above-mentioned sodium formate solution and the above-mentioned nickel acetylacetone solution were mixed and ultrasonically vibrated evenly, then added into a polytetrafluoroethylene reactor, sealed, and placed in a programmed temperature oven with a heating rate of 3°C / min. The mixture was reacted at 250°C for 1 h, cooled to room temperature, and the solids in the reaction mixture were separated by filtration. The mixture was washed alternately with water and ethanol for 3 times, vacuum dried at 60°C for 8 h, and then heat treated in air at 300°C for 15 min to obtain an electrolytic hydrogen evolution catalyst, which was defined as product 3.
[0037] Example 4 Weigh 0.4 g of sodium formate and add it to 5 ml of ultrapure water to obtain a sodium formate solution.
[0038] Weigh 0.3 g of ferric chloride and add it to 20 ml of a mixture of ethanol and water in a volume ratio of 1:1, and dissolve it by ultrasonication to obtain a ferric chloride solution.
[0039] 6 g of nitrogen-doped porous carbon material (purchased from Pioneer Nano, XFP14), the above-mentioned sodium formate solution and the above-mentioned ferric chloride solution were mixed and ultrasonically vibrated evenly, then added into a 50 ml polytetrafluoroethylene reactor, sealed, and placed in a programmed temperature oven with a heating rate of 1.5°C / min. The mixture was reacted at 200°C for 12 h, cooled to room temperature, and the solid in the reaction mixture was separated by filtration. The mixture was washed alternately with water and ethanol for 3 times, vacuum dried at 60°C for 8 h, and then heat treated in air at 350°C for 15 min to obtain an electrolytic hydrogen evolution catalyst, which was defined as product 4.
[0040] Example 5 Weigh 0.5 g of sodium formate and add it to 15 ml of ultrapure water to obtain a sodium formate solution.
[0041] Weigh 0.2 g of cobalt nitrate and add it to 15 ml of DMF for dissolution by ultrasonication to obtain a cobalt nitrate solution.
[0042] 5 g of nitrogen-doped porous carbon material (purchased from Pioneer Nano, XFP14), the above-mentioned sodium formate solution and the above-mentioned cobalt nitrate solution were mixed and ultrasonically vibrated evenly, then added into a 50 ml polytetrafluoroethylene reactor, sealed, and placed in a programmed temperature oven with a heating rate of 3°C / min. The reaction was carried out at 220°C for 12 h, cooled to room temperature, and the solid in the reaction mixture was separated by filtration. The solid was washed alternately with water and ethanol for 3 times, vacuum dried at 60°C for 8 h, and then heat treated in air at 280°C for 25 min to obtain an electrolytic hydrogen evolution catalyst, which was defined as product 5.
[0043] The electrolytic hydrogenation catalysts prepared in Examples 1-5 were characterized by scanning electron microscopy, XPS, etc. The results showed that these catalysts were porous particles with a particle size of about 1 to 100 μm, wherein catalytically active particles were distributed on the surface of the nitrogen-doped porous carbon material and inside the pores, wherein the catalytically active particles located on the surface of the nitrogen-doped porous carbon material were metal nanoparticles with a surface coated with a metal oxide with a thickness of about 5 to 10 nm, and the catalytically active particles located inside the nitrogen-doped porous carbon material were metal nanoparticles, and the particle size of these metal nanoparticles was in the range of 5 to 100 nm. Moreover, in these catalysts, the total mass of the catalytically active particles and the mass ratio of the nitrogen-doped porous carbon material were in the range of 1:10 to 100.
[0044] The performance test of the electrolytic hydrogenation catalyst (hereinafter referred to as catalyst) prepared in Examples 1-5 and Comparative Documents 1-2 was carried out, and the test items were as follows: Test item 1: Electrocatalytic water decomposition hydrogen production test, the test method is as follows: 0.5 parts by mass of catalyst, 0.05 parts by mass of flake graphite, 0.05 parts by mass of F-105 aqueous binder, 1 part by mass of water and 0.05 parts by mass of N-methylpyrrolidone were uniformly mixed and evenly coated on copper foil to prepare a working electrode.
[0045] A three-electrode test system was used on the electrochemical workstation CHI660E, including a working electrode, a graphite carbon sheet as a counter electrode, and a mercury-mercury oxide electrode as a reference electrode. The test electrolyte was a 25°C, 1 mol / L potassium hydroxide aqueous solution. High-purity nitrogen was passed through the test for saturation treatment, and the test temperature was room temperature. During the linear sweep voltammetry test, the scan rate was 1 mV / s, and the solution ohmic drop iR compensation correction was performed, and the electrode potential was converted to the reversible hydrogen electrode (RHE). The stability test results were recorded through the potential-time curve.
[0046] Test item 2: Water decomposition performance test, the test method is as follows: According to the method of Test Item 1, the electrolytic hydrogen evolution catalysts in Examples 1-5 and Comparative Documents 1-2 were respectively made into working electrodes.
[0047] The nickel foam catalyst coated with nickel disulfide was used as the catalyst for oxygen evolution in the complete water splitting process, and the above working electrode was used as the catalyst for hydrogen evolution electrolysis. The catalyst was assembled into a complete water splitting electrolysis hydrogen evolution catalyst and installed in a self-designed large-area complete water splitting device for water splitting performance testing. Test method: A two-electrode test system was used on the electrochemical workstation CHI660E. The test electrolyte was a 25°C, 1 mol / L potassium hydroxide aqueous solution. The test temperature was room temperature. When testing the linear sweep voltammetric curve, the scan rate was 2mV / s.
[0048] The test results of the above test items 1 and 2 are shown in the following tables 1 and 2 respectively.
[0049] Table 1 Water decomposition performance test results of the products of Examples 1-5 and Comparative Documents 1-2 ; Table 2 Test results of electrocatalytic water decomposition and hydrogen production of the products of Examples 1-5 and Comparative Documents 1-2
[0050] The specific embodiments described in the present invention are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the attached claims.
[0051] Although the present invention has been described in detail and some specific embodiments have been cited, it is obvious to those skilled in the art that various changes and modifications can be made without departing from the spirit and scope of the present invention.
Claims
1. A catalyst for electrolytic hydrogen evolution, characterized in that: include: Nitrogen-doped porous carbon materials; first catalytically active particles, which are distributed on the surface of the nitrogen-doped porous carbon material, and include first transition metal nanoparticles and a transition metal oxide layer coated on the surface of the first transition metal nanoparticles; The second catalytically active particles are distributed in the pores contained in the nitrogen-doped porous carbon material and include second transition metal nanoparticles.
2. The electrolytic hydrogen evolution catalyst according to claim 1, characterized in that: The molar ratio of C element to N element contained in the nitrogen-doped porous carbon material is 100:5-15, the porosity is 80-95%, and the pore size of the contained pores is 30-150 nm; and / or the particle size of the nitrogen-doped porous carbon material is 1-100 μm.
3. The electrolytic hydrogen evolution catalyst according to claim 1, characterized in that The materials of the first transition metal nanoparticles and the second transition metal nanoparticles include copper, iron, nickel, titanium or cobalt; and / or the particle sizes of the first transition metal nanoparticles and the second transition metal nanoparticles are 5-100 nm.
4. The electrolytic hydrogen evolution catalyst according to claim 1, characterized in that: The thickness of the transition metal oxide layer is 5-10 nm.
5. The electrolytic hydrogen evolution catalyst according to claim 1, characterized in that: The mass ratio of the total mass of the first catalytically active particles and the second catalytically active particles in the electrolytic hydrogen evolution catalyst to the nitrogen-doped porous carbon material is 1:10-100.
6. A method for preparing the electrolytic hydrogen evolution catalyst according to any one of claims 1 to 5, characterized in that: include: A mixed reaction system comprising nitrogen-doped porous carbon material, soluble transition metal salt, small molecule organic acid salt, water and organic solvent is subjected to solvothermal reaction at 150-250° C. for 0.5-12 h, and then the solid in the obtained reaction mixture is separated, washed and vacuum dried in sequence, and then heat treated in air at 250-400° C. for 10-30 min to obtain the electrolytic hydrogenation catalyst.
7. The preparation method according to claim 6, characterized in that: The mass ratio of the nitrogen-doped porous carbon material, the soluble transition metal salt, the small molecule organic acid salt, water and the organic solvent is 10-100:1-2:1-2:10-600:10-300.
8. The preparation method according to claim 6, characterized in that: The soluble transition metal salt is at least selected from chlorides, nitrates, sulfates or organic acid salts of copper, iron, nickel, titanium or cobalt.
9. The preparation method according to claim 6, characterized in that: The small molecule organic acid salt includes sodium formate, potassium formate, sodium acetate or potassium acetate.
10. A method for producing hydrogen by electrocatalytic water decomposition, characterized in that: The working electrode used in the method comprises the electrolytic hydrogen evolution catalyst according to any one of claims 1 to 5.